Creating Civilization: Integrating The Anima and Becoming Wise - Martha C. Beck (Pusat Studi Gender dan Anak, 2020)
This paper will begin, but only begin, to discuss the ways the Greek pantheon of goddesses is described in myth and tragedy, and show that the realm of Greek divinities is a realm of patriarchy, of male domination. The myths and tragedies expose the ways men do great harm while at the same time ignorng or denying the real impact of their behavior. Presenting these myths and tragedies people can learn the characters and recognize thir own ability to do harm and will change. This paper will give a very brief description of the seven goddesses of Greek mythology taken from the book, Goddesses in Everywoman, by Jean Shindola Bolen. Examples are selected that show both positive and negative, creative and destructive aspects of each goddess. This paper concludes that the seven archetypes are powerful psychological forces in the souls of women, which in a patriarchal culture, the positive drive side is frustrated or destroyed and the destructive side emerges as a response to this unjust suffering. The purpose of this paper has been to describe the many dimensions of the anima force in women’s psyches so that everyone, men and women, can work toward creating a less patriarchal society.